Storytelling and English language teaching: an approach using japanese folk narratives and Amazon region stories - SILVA, Marcos Gabriel Cardoso (2024)
This work refers to storytelling teaching approach, using folk narratives as the main didactic and intercultural element. The main objective is to analyze the narrative productions of A1 level students from a free English language course at the Federal University of Pará. The theoretical perspectives are divided into four sections referring to: the elements of the narrative, highlighting the proposals of Meyer and Miller (2019) and Gill (1985), which were used in the construction of the narratives; interculturality as an approach to foreign language teaching, according the concepts by Kramsch (1993) and Candau (2019); to anime used as authentic materials and to the concepts of myths, legends and folklore, also used as educational resources in the teaching approach of this work. The methodology used followed a qualitative approach of an exploratory nature and participant observation, conducted through a project applied in the classroom, in which anime were used as authentic materials portraying Japanese folklore, folk narratives from the Amazon region and narrative elements used as an object of study for students' storytelling, in textual format and in English. Finally, it was understood that storytelling as a teaching approach was positively effective, together with the use of anime and folkloric narratives from the Amazon.